The Art of Maude J. Mitchell (1875-1957) - Carol Cook (Symphony in the Flint Hills, 2011)
Maude Josephine Mitchell was the daughter of early Wabaunsee County pioneers Captain William and Mary Mitchell. Captain Mitchell was a leader of the Beecher Bible and Rifle Colony who came to the area in 1856. He operated an Underground Railroad station at his home three miles east of the town of Wabaunsee. Maude was a very famous Kansas artist who strived to capture the pure beauty of the land and all that it contained.
Keywords: Maude Mitchell; art; Kansas; Wabunsee; Captain William; Mary Mitchell; Beecher Bible and Rifle Colony; pioneer; Underground Railroad; public schools; Platteville State Normal School; New York State Normal College; Manhattan; New York City; Pottawatomie County; architecture; landscape; Flint Hills; watercolor; post-Civil War; black; settlement; Prairie Roads a Windin; murals; Columbia University